2002
DOI: 10.1017/s104795110200077x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and risk factors for late deaths in tetralogy of Fallot: the Japanese Nationwide Multicentric Survey

Abstract: Late survival was excellent, with a low incidence of reoperations in both groups of patients. The era of repair has a big influence on total and operative mortality, but has only a small impact on late mortality. Ongoing analysis of follow-up will possibly reveal subsequent changes with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Residual pulmonary regurgitation in patients with TOF after repair is the major responsible factor for right ventricular dilatation, ventricular tachycardia and sudden death [16]; on the contrary, in patients with the RV to RA conduit repair, right ventricular hypertension because of residual progressive right ventricular outflow stenosis is a predictive factor for VT/Vf/SD. Mortality due to pulmonary regurgitation in patients with repaired TOF was reported to be a late phenomenon [18], but the VT/Vf/ SD was observed relatively early after repair [19] as observed in our study. There is no gold standard to quantify PR after external conduit repair other than MRI and only limited number of patients had MRI for this purpose in this study.…”
Section: Predictive Factors For Arrhythmias and Sudden Deathsupporting
confidence: 77%
See 1 more Smart Citation
“…Residual pulmonary regurgitation in patients with TOF after repair is the major responsible factor for right ventricular dilatation, ventricular tachycardia and sudden death [16]; on the contrary, in patients with the RV to RA conduit repair, right ventricular hypertension because of residual progressive right ventricular outflow stenosis is a predictive factor for VT/Vf/SD. Mortality due to pulmonary regurgitation in patients with repaired TOF was reported to be a late phenomenon [18], but the VT/Vf/ SD was observed relatively early after repair [19] as observed in our study. There is no gold standard to quantify PR after external conduit repair other than MRI and only limited number of patients had MRI for this purpose in this study.…”
Section: Predictive Factors For Arrhythmias and Sudden Deathsupporting
confidence: 77%
“…There were several studies regarding the incidence of arrhythmia and sudden death in patients with repaired TOF [16,18,26]. However the data after external conduit repair are more limited.…”
Section: Incidence Of Arrhythmiasmentioning
confidence: 99%
“…Because of poor unoperated survival and high surgical death rates in Japan before the 1970s, most patients with complex CHD, except those with tetralogy of Fallot (TOF), died before their first year of life [4,5]. Even in TOF, the operative mortality rate was as high as 27% in 1972 according to a Japanese multicenter study [5].…”
Section: Mortality For Severe Chd Until The1970smentioning
confidence: 99%
“…Previous studies have shown that the clinically important arrhythmias are associated with older age at repair, 4,8,10,[12][13][14][15] large ventriculotomy, 10 high postoperative right ventricular pressure, 8,10,[12][13][14] tricuspid and/or pulmonary regurgitation, 2,12,15-17 cardiomegaly 2,18 or long QRS duration. 2,3,18 We therefore included these parameters in the data file for the analysis of risk factors.…”
Section: Subjectsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] In Japan, Kobayashi et al reported a single institute's experience of arrhythmias analyzed by Holter monitor in postoperative TOF, 9 and recently, Niwa et al reported a Japanese survey on the quality of life in adult patients with postoperative TOF, including some data on arrhythmias. 10 These Japanese studies, however, are not comparable with the studies from Western countries in terms of the number of subjects and length of follow-up. We therefore organized a multicenter study group in Japan in order to demonstrate the prevalence of clinically important arrhythmias, the risk factors of the arrhythmias, and the significance of the arrhythmias in major morbidity and late mortality in patients after repair of TOF.…”
mentioning
confidence: 90%